2009
DOI: 10.1524/ract.2009.1635
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of iodine into uranophane formed during the corrosion of spent nuclear fuel

Abstract: In order to evaluate the potential incorporation of 129 I into uranyl phases that would form during oxidative alteration of spent nuclear fuel, uranophane was synthesized under mild hydothermal conditions of 165 • C in the presence of iodide, iodate and periodate, respectively. The precipitates were examined and analyzed using powder X-ray diffraction (XRD), infrared spectroscopy (IR) and scanning electron microscope (SEM) equipped with an energy-dispersive X-ray spectroscopy (EDS). The results indicate that s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…Iodine-129 is one of the fission products in nuclear wastes, with a long half-life of 1.7 × 10 7 years. It was found that the initial formation of actinide iodate complexes or the incorporation of iodate anions in actinide-bearing minerals may occur after the accidental release of actinides and fission products. Therefore, the structures, thermostability, and spectroscopic properties of actinide iodates have been extensively explored during the past 2 decades. , Among these, rare coordination features were observed in both actinide- and iodine-based compounds, such as the hexaoxoiodate­(VII), cation–cation interactions between neptunyl units, where the axial oxygen of the actinyl unit further binds to another metal cation and acts as a bridging oxo atom, and tetraoxoiodate­(V) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Iodine-129 is one of the fission products in nuclear wastes, with a long half-life of 1.7 × 10 7 years. It was found that the initial formation of actinide iodate complexes or the incorporation of iodate anions in actinide-bearing minerals may occur after the accidental release of actinides and fission products. Therefore, the structures, thermostability, and spectroscopic properties of actinide iodates have been extensively explored during the past 2 decades. , Among these, rare coordination features were observed in both actinide- and iodine-based compounds, such as the hexaoxoiodate­(VII), cation–cation interactions between neptunyl units, where the axial oxygen of the actinyl unit further binds to another metal cation and acts as a bridging oxo atom, and tetraoxoiodate­(V) .…”
Section: Introductionmentioning
confidence: 99%
“…It was found that the initial formation of actinide iodate complexes or the incorporation of iodate anions in actinide-bearing minerals may occur after the accidental release of actinides and fission products. Therefore, the structures, thermostability, and spectroscopic properties of actinide iodates have been extensively explored during the past 2 decades. , Among these, rare coordination features were observed in both actinide- and iodine-based compounds, such as the hexaoxoiodate­(VII), cation–cation interactions between neptunyl units, where the axial oxygen of the actinyl unit further binds to another metal cation and acts as a bridging oxo atom, and tetraoxoiodate­(V) . A series of functional materials with potential applications such as nonlinear-optical (NLO) materials (primarily due to stereochemically active lone-pair electrons in the iodate unit), selective ion-exchange properties, and intercalation of the neutral molecules of HIO 3 or KCl have also been prepared. ,, Furthermore, structural deviation was shown in the hexavalent uranium, neptunium, ,,, and plutonium series and the trivalent americium, curium, , and californium series, which originates from the discontinuity in their chemical properties entailing solubilities, redox potentials, electron orbital involvement, etc.…”
Section: Introductionmentioning
confidence: 99%
“…In the reported iodate substitution, both the SiO 4 and PO 4 polyhedra are isolated with other SiO 4 or PO 4 polyhedra [27][28][29]. In contrast, the BO 3 or BO 4 polyhedra in KUB and NaUB structure are connected to other BO 3 or BO 4 polyhedra to form framework.…”
Section: La-icp-msmentioning
confidence: 98%
“…The trace amount of iodine in KUB samples may be contributed by iodine inclusion, or intercalated between the layers. Generally, anions with similar valences and geometries can easily substitute for one another, such as ( [27,28]. However, the length of I-O bond ranges between 1.77 Å and 1.86 Å and is much longer than the B-O bond (1.36-1.49 Å).…”
Section: La-icp-msmentioning
confidence: 99%
See 1 more Smart Citation